Efektivitas Model Pembelajaran PJBL Terhadap Hasil Belajar Peserta Didik Pada Materi Pencemaran Lingkungan Terintegrasi Keislaman - Sri Lestari; Efrida Pima Sari Tambunan; Irwan Syahputra (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
The use of learning models that are less precise and do not vary the impact on learning outcomes for low learners. This study aims to determine the effectiveness of the PJBL learning model on the learning outcomes of integrated environmental pollution Islamic material. The study was conducted at MAN Tebing Tinggi in July. This type of research is quantitative. This research used a quasi-experiment with a pretest-posttest control group design. The research sample of two classes of PMIPA 1 and PMIPA 2 in Man Tebing Tinggi was collected using simple random sampling techniques and subject analysis with 72 students. Test instruments used in the form of test questions conducted at the beginning of learning (pretest) and the end of learning (posttest) include as many as 25 questions. Data analysis of student learning outcomes with the data processing software SPSS 21 using the formulas T-test and N-gain test Based on the hypothesis test obtained, the learning model of PjBL affects the learning outcomes of students' understanding of environmental pollution material in Man Tebing Tinggi with a t-test of 0.230. The N-Gain test results showed that the PjBL learning model was effective in improving the learning outcomes of students in the Islamic integrated environmental pollution material at MAN Tebing Tinggi, with an N-Gain of 0.72 in the high category.